Federalism and European Union after Maastricht - Denton, Geoffrey (HMSO LondonGB, 1993)
Discusses the federalist practice and experience of Germany and Switzerland; the centralising system and tendencies in France and the United Kingdom; and, the difficulties of adaption of member states with constitutional and political experiences to a single European 'federal' model.